Analisis Deiksis Sosial pada Isi Teks Berita Surat Kabar Online Radar Tegal - Alfina Damayanti; Ghufroni; Tri Linda Antika (PT. Penerbit Tiga Mutiara, 2026)
This study is motivated by the use of language in news reports, which not only conveys information but also represents respect, identity, status, social relationships, and the authority of the actors involved. This study aims to describe the forms and functions of social deixis and the influence of social context on its use in Radar Tegal news reports, focusing on honorific, relational, and absolute categories. The study employs a qualitative descriptive approach and pragmatic analysis, using news reports from the February 2026 edition of Radar Tegal as the data source, which were collected through observation and note-taking methods and analyzed through selection, classification, interpretation, and verification. The findings reveal six instances of social deixis, equally distributed into two honorific, two relational, and two absolute forms, each accounting for 33.33%; Pak Gubernur and Gus Ipul indicate respect and social closeness, saya and pedagang represent relationships and professional identities, while institutional positions emphasize authority. In conclusion, social deixis cannot be determined solely based on linguistic forms but must be understood through social context and relationships among participants, with the novelty of this study lying in its analysis of deixis that connects linguistic forms with the social positions of news actors.